The Implementation of Corruption Crime from the Perspective of Tafsir and Hadith - Akhmadi, Nurman; Hanafi, Sahrul; Ridwan, Ahmad Hasan (Fast in Social Sciences, 2025)
The crime of corruption is an extraordinary crime that has a broad impact on the morality of the nation, social justice, and the sustainability of national development. In the Islamic perspective, corruption is not only seen as a violation of positive law, but also as an act of great sin that contains elements of betrayal of trust and creates social damage (fasad fil-ardh). Therefore, handling corruption is not sufficient through legal instruments alone, but also requires a moral and spiritual approach based on the values of the Qur'an and hadith. This article aims to examine the implementation of corruption crimes in the perspective of tafsir and hadith by examining Qur'anic verses related to the concepts of ghulul (betrayal), risywah (bribery), sariqah (theft), and hirabah (robbery), as well as traditions that condemn similar behavior. This study uses a normative qualitative approach with thematic interpretation (mauḍu'i) and hadith analysis methods to find Islamic universal values in the prevention and eradication of corruption. The results of the study show that the implementation of the crime of corruption in the perspective of tafsir and hadith is a moral and spiritual deviation that is contrary to Islamic teachings. The Qur'an describes corruption through the terms ghulul (embezzlement), risywah (bribery), which will cause fasad fil-ardh (damage), all of which indicate the unauthorized deprivation of other people's rights. QS. Al-Baqarah: 188 prohibits consuming wealth through unlawful means, while the Hadith narrated by Bukhari No. 3196 emphasizes severe punishment for the perpetrators. Corruption is a grave sin that violates the principles of trust and justice, so its eradication must be through strict law enforcement and moral guidance based on the values of the Qur'an and hadith.